1994
DOI: 10.1007/bf01719573
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of abdominal symptoms in a random population: Prevalence, incidence, and natural history

Abstract: The study presents results from a five-year follow-up on abdominal symptoms in an age and sex stratified random sample of 4,581 Danes. Abdominal pain occurred significantly more often among women (prevalence: 49%, incidence: 21%) compared to mean (prevalence: 38%, incidence: 15%). Five years later the pain had disappeared in 43% of the men and 31% of the women (p = 0.003). Distension, borborygmi, and altering consistency of stools occurred with a prevalence of approximately 50% and an incidence of approximatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
2
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 29 publications
3
39
2
5
Order By: Relevance
“…However, despite these limitations, our findings are in accordance with population-based studies from various Western nations. 3,7,18,24,[34][35][36] In summary, there are marked differences in the country specific prevalence of UGI complaints. These differences are associated with socioeconomic indicators such as the GDP per capita.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite these limitations, our findings are in accordance with population-based studies from various Western nations. 3,7,18,24,[34][35][36] In summary, there are marked differences in the country specific prevalence of UGI complaints. These differences are associated with socioeconomic indicators such as the GDP per capita.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Studies from specific countries and post hoc analyses reported that the prevalence of dyspepsia (upper) abdominal pain and the severity of reflux symptoms decreases with advancing age. [6][7][8][9] However, despite their decreasing overall prevalence, more serious GERD-complications like complicated ulcers (i.e. life-threatening bleeding) and adenocarcinoma 10 appear to occur predominantly in elderly patients.…”
Section: Introductionmentioning
confidence: 99%
“…Alguns estudos encontraram maior risco para homens (1,5) , outros para mulheres (7) . Em todos os estudos revisados, os riscos relativos tanto para homens, quanto para mulheres são pequenos, nunca superiores a 1,5, o que pode sugerir que o sexo é pouco importante na determinação da ocorrência de sintomas de DRGE.…”
Section: Discussionunclassified
“…A ausência de associação entre DRGE e indivíduos não-brancos é consistente com o achado de outros autores, uma vez que estudos em diferentes partes do mundo não têm encontrado relação com raça ou cor da pele (1,5,10) . O aumento do risco para desenvolvimento de sintomas de DRGE conforme diminui a faixa etária, encontrado neste estudo, é coerente com oa achados na Austrália (5) .…”
Section: Discussionunclassified
See 1 more Smart Citation